2022
DOI: 10.1083/jcb.202202030
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical insights into lipid transport by VPS13 proteins

Abstract: VPS13 proteins are proposed to function at contact sites between organelles as bridges for lipids to move directionally and in bulk between organellar membranes. VPS13s are anchored between membranes via interactions with receptors, including both peripheral and integral membrane proteins. Here we present the crystal structure of VPS13s adaptor binding domain (VAB) complexed with a Pro-X-Pro peptide recognition motif present in one such receptor, the integral membrane protein Mcp1p, and show biochemically that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 45 publications
6
78
1
Order By: Relevance
“…The structures of XKR8 and XKR9 were recently solved by Cryo-EM(34, 35). AlphaFold2-based prediction(20, 33) of the structure of XK suggests an overall very similar fold (10)and thus a similar scramblase function, as confirmed by recent in vitro studies(13). However, XK differs from XKR8 and XKR9 in the cytosolic loops and C-terminal tail.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The structures of XKR8 and XKR9 were recently solved by Cryo-EM(34, 35). AlphaFold2-based prediction(20, 33) of the structure of XK suggests an overall very similar fold (10)and thus a similar scramblase function, as confirmed by recent in vitro studies(13). However, XK differs from XKR8 and XKR9 in the cytosolic loops and C-terminal tail.…”
Section: Discussionsupporting
confidence: 68%
“…Accordingly, there is evidence for the partnership of the chorein motif protein ATG2 with lipid scramblases in the growth of the autophagosome membrane(4, 11, 12). A cooperation between VPS13A and XK, which has been recently confirmed to have scramblase activity by in vitro studies(13), would represent another example of such partnership, providing clues to mechanisms of disease in chorea-acanthocytosis and McLeod syndrome. Strong support for this possibility came by the demonstration of an interaction between these two proteins: i) studies of McLeod syndrome erythrocytes revealed that lack of XK results in a loss of VPS13A in their membranes(8), as expected if VPS13 and XK are part of a same complex; ii) their interaction was supported by biochemical experiments(810); iii) the localization of overexpressed VPS13A at contacts between ER and lipid droplets was shown to abolished by co-overexpression of XK resulting in a localization VPS13A along with XK throughout the ER(9).…”
Section: Introductionmentioning
confidence: 97%
“…XK encodes a lipid scramblase, capable of flipping individual phospholipids between the leaflets of a membrane bilayer (Adlakha et al, 2022; Ryoden et al, 2022). XK is required for extracellular exposure of phosphatidylserine in response to extracellular ATP in immune cells and VPS13A is necessary for XK activity in this context (Ryoden et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Physical interaction with lipid scramblases has emerged as a common property of VPS13-family and related lipid transport proteins (Adlakha et al, 2022; Ryoden et al, 2022). This linking of intermembrane and intrabilayer transport may be important for promoting transport through the VPS13 channel by maintaining a concentration gradient in lipids between the donor and acceptor leaflets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation